Approaches to the development of the competence model of a high school graduate (Journal of Educational Sciences, 2022)
In this scientific article considers in depth the approaches to the development of the competence model of modern bilimdаr urpak. The competencies necessary for improving the education system are given clearly. The authors emphasize the need to evaluate the result of learning knowledge and specify whether to return to the content of education or to the activity of a teacher if the result is not satisfactory. Based on the results of a questionnaire conducted by methodological centers of the Republic, the competencies need to be found in a generation motivated to education. are described in detail. In order to develop students knowledge, skills, abilities and the necessary competencies  the subject, content, activity that forms each competence or skill were determined. In order to improve the quality of education the authors analysed the personal qualities and evaluation criteria of a graduate of primary school and secondary school. In order to improve the quality of modern education the authors analyze the criteria for assessing the specified personal qualities and knowledge of a secondary school graduate. Dedication of research work to the problems of pedagogical qualimetry in Kazakhstan determines its scientific significance, practical significance for determining the criteria for assessing the competence model of a secondary school graduate.Keywords: bilimdаr urpak (generation motivated to education); personality, competence, competence model, content of education, quality of education, assessment, social order, model of primary school, model  of secondary school.